AESTHETIC EXPERIENCE AS A CONDITION OF ARTISTIC PERCEPTION OF LITERARY TEXT IN LITERARY READING LESSONS IN ELEMENTARY SCHOOL - Oboroceanu, Viorica (International Journal of Innovative Technologies in Social Science, 2020)
In the frame of literary texts, different values interact. This way, the interpretation of a literary text will include the pupil into various interpretative activities, thus forming its attitude. Attitude is the understanding of the individual to assess an object, its symbol, or a certain aspect of the world. Whether positive or negative, attitude shows what position the person takes regarding the existing system of values, norms and principles in the society.The literary work is by excellence an attitude generator. The text gives the opportunity to the pupil to assess new things, gradually passing and connecting previous ideas to the new ones. Meanwhile the reading process, the essential properties of the text and their relations with the new things are discovered. So, new ideas become intelligible for the pupil’s understanding.The study of the literary text in the primary classes is performed in a complex manner. It provides not only comprehension, perception, analysis, interpretation and appreciation of reading, but also transfers literary-artistic and linguistic-communicative understanding into new situations, detached from everyday life with an individual approach.